New Dicranoptycha Osten Sacken, 1859 Crane flies (Diptera: Limoniidae) of North and South Korea - Podenas, Sigitas; Byun, Hye-Woo; Kim, Sam-Kyu (Zootaxa, 2015)
Two new species of Dicranoptycha Osten Sacken, 1859, crane flies (Diptera, Limoniidae) from the Korean peninsula are described, illustrated and compared with already known and related species. An identification key and check-list of all Korean Dicranoptycha is presented.